2021
DOI: 10.1159/000511661
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes Associated with the Development of Acute Kidney Injury by Weighted Gene Co-Expression Network Analysis

Abstract: <b><i>Background:</i></b> Acute kidney injury (AKI) is a severe clinical syndrome, causing a profound medical and socioeconomic burden worldwide. This study aimed to explore underlying molecular targets related to the progression of AKI. <b><i>Methods:</i></b> A public database originated from the NCBI GEO database (serial number: GSE121190) and a well-established and unbiased method of weighted gene co-expression network analysis (WGCNA) to identify hub genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Some studies have shown that the increase of FBG levels is an important stage that directly or indirectly leads to the occurrence and death of cardiovascular events [ 8 ]. AST, ALT, BUN, Cr, and so on are among the most commonly used indexes for detecting liver and renal function in clinics [ 9 , 10 ]. The levels of AST, ALT, BUN, and Cr increased obviously when the liver and kidney were damaged.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the increase of FBG levels is an important stage that directly or indirectly leads to the occurrence and death of cardiovascular events [ 8 ]. AST, ALT, BUN, Cr, and so on are among the most commonly used indexes for detecting liver and renal function in clinics [ 9 , 10 ]. The levels of AST, ALT, BUN, and Cr increased obviously when the liver and kidney were damaged.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically significant modules were identified by calculating the correlation between ME and clinical trait, and the degree of connection was measured. Gene significance (GS) was used to evaluate this degree and a higher GS indicated the increased significance of genes 10–12 …”
Section: Methodsmentioning
confidence: 99%
“…Gene significance (GS) was used to evaluate this degree and a higher GS indicated the increased significance of genes. 10 , 11 , 12 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent multiple experimental analyses indicated that Rplp1 significantly upregulated display dramatically increased in the kidneys of Cis-AKI and display dramatically increased after 3 days and decreased after 7 days ( Lin et al, 2021 ). Moreover, a previous study focused on the relationship between the expression of TIMP1 and the incidence of sepsis-associated acute kidney injury (SAAKI).…”
Section: Introductionmentioning
confidence: 99%